Scintillation pulse shape discrimination with CaWO₄, ZnWO₄, and CdWO₄ crystal - Danevich, F.A.; Georgadze, A.Sh.; Kobychev, V.V.; Kropivyansky, B.N.; Nagorny, S.S.; Nikolaiko, A.S.; Tretyak, V.I.; Yurchenko, S.S.; Zdesenko, S.Yu.; Zdesenko, Yu.G.; Bizzeti, P.G.; Fazzini, T.F.; et al. (Functional Materials, 2005)
The time properties of scintillation pulse form for у rays and α particles in CaW0₄, ZnW0₄, and CdW0₄ crystal have been investigated. А method for discrimination of various particle types using the pulse shape distinctions has been developed. А complete signal separation for у quanta and α particles has been attained. The pulse shape dependences on the α irradiation energy (for all the crystals) and direction in relation to the main crystallographic axes (for ZnW0₄ and CdW0₄ scintillators) have been observed and studied. The temperature dependence of the average decay time of CdW0₄ for у rays and α particles has been measured in temperature interval 0-30 ℃.